Report of the Coming-of-Age Conference held at Bradford, April, 1914. (London : Independent Labour Party, 1914)
Bibliotheek Camille Huysmans
Vermeldingen van Camille Huysmans als spreker op p. 51, 59, 62 en 133
Engels
Monografie
Keywords: Labour Party; Groot-Brittannië.